The message of Ephesians : God's new society - Stott, John R.W., (John Robert Walmsley), 1921-2011. (Leicester, UK : IVP, 1979)
Includes bibliographical references.
"The Bible Speaks Today" series has been placed in the library in memory of Gordon W. Craig, 1926-1990
Keywords: Bible. -- commentaries